2016
DOI: 10.4238/gmr.15028786
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive LC-MS/MS method for the determination of auraptene in rat plasma and its application in a pharmacokinetic and bioavailability study in rats

Abstract: ABSTRACT.A simple, sensitive and specific liquid chromatographytandem mass spectrometry method was developed and validated for the determination of auraptene, a constituent isolated from Fructus aurantii with potential to combat Alzheimer's disease, in rat plasma. Rat plasma samples were pretreated by protein precipitation with methanol. The analytes were separated by a Waters Sun Fire C18 column (50 mm x 2 mm, 5 µm) and eluted with 1:1000 methanol and formic acid/water (v/v) mobile phase with a flow rate of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…After auraptene (100 mg/kg, p.o.) administration to rats, the maximum plasma concentration was previously reported to be 1.72 ± 0.38 µg/mL [ 26 ]. As the content of auraptene in CHEP was 80%, its maximum plasma concentration after administration of 300 mg/kg/day p.o., was supposed to be 5.16 µg/mL in our in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…After auraptene (100 mg/kg, p.o.) administration to rats, the maximum plasma concentration was previously reported to be 1.72 ± 0.38 µg/mL [ 26 ]. As the content of auraptene in CHEP was 80%, its maximum plasma concentration after administration of 300 mg/kg/day p.o., was supposed to be 5.16 µg/mL in our in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, oral administration of osthenol to ICR mice at a dose of 5 mg/kg and 20 mg/kg resulted in the following PK parameters: C max of 66.1 ± 3.2 and 56.0 ± 29.1 ng/mL, respectively, and T max of 36.3 ± 13.8 and 6.3 ± 1.3 min, respectively, indicating the very low bioavailability of the compound as well as its non-linear pharmacokinetics [22]. Oral administration of auraptene to rats at a dose of 100 mg/kg provided the maximum concentration of the compound in blood plasma of 1719 ± 384.3 ng/mL and T max of 108.0 ± 25.3 min, and the bioavailability of auraptene was determined to be 8.5% [23]. Taking into account the data mentioned above, we suppose that the agent K-142 can be metabolized rapidly after administration to animals and metabolized in the first pass, and the search for metabolites of K-142 will be the objective of our next studies.…”
Section: Pharmacokinetics Study Of K-142 After Oral Administration To...mentioning
confidence: 99%
“…Ye et al determined the pharmacokinetics of auraptene in rat plasma using LC-MS/MS method. Data showed that a dose range of 0.5–200 ng/ml of auraptene was safe and bioavailability of oral administration of auraptene was merely 8.5% in rats ( Ye et al, 2016 ). In another study, the absorption and metabolism of auraptene in rodent models was examined.…”
Section: Pharmacokinetics Of Auraptenementioning
confidence: 99%